In-vivo anti-tumor activities of curcumin-solid-dispersion loaded floating tablets on stomach and lung cancers - Duyen Thi My Huynh, Van De Tran, Suchiwa Pan-On, Duy Toan Pham (Journal of Applied Pharmaceutical Science, 2024)
Curcumin, a natural compound commonly found in turmeric (Curcuma longa L.), has been proven effective in stomach and lung cancer treatment. However, due to its poor solubility in water and instability in alkaline medium, curcumin oral application is still limited. Thus, in this study, a curcumin-solid-dispersion (CSD) loaded floating tablet was successfully developed and evaluated for its anti-cancer properties against lung and stomach cancer in an in-vivo setting in mice. The results demonstrated that the CSD-loaded floating tablets did not exhibit acute oral toxicity in healthy mice at maximum doses of ~10 g/kg body weight. Moreover, tested in a carcinogenic mice model induced with 7,12-dimethyl benz[a]anthracene, the tablets could significantly inhibit the growth of stomach/lung cancer cells and reduce the cancer rate up to ~40%, comparable to that of the standard drug 5-fluorouracil (5-FU). In addition, the CSD-loaded floating tablets could complement the drug 5-FU efficacy in treating stomach/lung cancers, with a cancerous tumor reduction rate of ~65%. Finally, the research confirmed that using the tablet in the early stages would reduce the cancer rate better than using it in the late stages. In conclusion, the CSD-loaded floating tablets showed much potential as an oral dosage form for stomach and lung cancer treatments.
Keywords: Cucurmin, solid dispersion, floating tablet, in-vivo, lung cancer, stomach cancer